Photoredox/Nickel‐Catalyzed Single‐Electron Tsuji–Trost Reaction: Development and Mechanistic Insights. (7th November 2018) - Matsui, Jennifer K.; Gutiérrez‐Bonet, Álvaro; Rotella, Madeline; Alam, Rauful; Gutierrez, Osvaldo; Molander, Gary A.
Abstract: A regioselective, nickel‐catalyzed photoredox allylation of secondary, benzyl, and α‐alkoxy radical precursors is disclosed. Through this manifold, a variety of linear allylic alcohols and allylated monosaccharides are accessible in high yields under mild reaction conditions. Quantum mechanical calculations [DFT and DLPNO‐CCSD(T)] support the mechanistic hypothesis of a Ni 0 to Ni II oxidative addition pathway followed by radical addition and inner‐sphere allylation.